Performance comparison and sustainability assessment of mesoporous FAU zeolites for the plastic upcycling - Muhammad Usman Azam; Nanbyen George Kim; Auguste Fernandes; M. Filipa Ribeiro; Waheed Afzal; Inês Graça (Chemical Engineering Journal, 2026)

Unlocking the structure-activity relationship of hierarchical MFI zeolites towards the hydrocracking of HDPE - Muhammad Usman Azam; Auguste Fernandes; Maria João Ferreira; Alan J. McCue; Inês Graça; Waheed Afzal (Fuel, 2025)

Hydrocracking of surgical face masks over Y Zeolites: Catalyst development, process design and life cycle assessment - Muhammad Usman Azam; Auguste Fernandes; Inês Graça; Waheed Afzal (Fuel, 2023)

Population genomics of introduced Nile tilapia Oreochromis niloticus (Linnaeus, 1758) in the Democratic Republic of the Congo: Repeated introductions since colonial times with multiple sources - Mare Geraerts; Carl Vangestel; Tom Artois; Jorge Manuel de Oliveira Fernandes; Michiel W. P. Jorissen; Auguste Chocha Manda; Célestin Danadu Mizani; Karen Smeets; Jos Snoeks; Gontran Sonet; Yang Tingbao; Maarten Van Steenberge; et al. (Molecular Ecology, 2022)
During colonial times, Nile tilapia Oreochromis niloticus (Linnaeus, 1758) was introduced into non‐native parts of the Congo Basin (Democratic Republic of the Congo, DRC) for the first time. Currently, it is the most farmed cichlid in the DRC, and is present throughout the Congo Basin. Although Nile tilapia has been reported as an invasive species, documentation of historical introductions into this basin and its consequences are scant. Here, we study the genetic consequences of these introductions by genotyping 213 Nile tilapia from native and introduced regions, focusing on the Congo Basin. Additionally, 48 specimens from 16 other tilapia species were included to test for hybridization. Using RAD sequencing (27,611 single nucleotide polymorphisms), we discovered genetic admixture with other tilapia species in several morphologically identified Nile tilapia from the Congo Basin, reflecting their ability to interbreed and the potential threat they pose to the genetic integrity of native tilapias. Nile tilapia populations from the Upper Congo and those from the Middle–Lower Congo are strongly differentiated. The former show genetic similarity to Nile tilapia from the White Nile, while specimens from the Benue Basin and Lake Kariba are similar to Nile tilapia from the Middle–Lower Congo, suggesting independent introductions using different sources. We conclude that the presence of Nile tilapia in the Congo Basin results from independent introductions, reflecting the dynamic aquaculture history, and that their introduction probably leads to genetic interactions with native tilapias, which could lower their fitness. We therefore urge avoiding further introductions of Nile tilapia in non‐native regions and to use native tilapias in future aquaculture efforts.